2020
DOI: 10.1073/pnas.1908100117
|View full text |Cite
|
Sign up to set email alerts
|

Active efficient coding explains the development of binocular vision and its failure in amblyopia

Abstract: The development of vision during the first months of life is an active process that comprises the learning of appropriate neural representations and the learning of accurate eye movements. While it has long been suspected that the two learning processes are coupled, there is still no widely accepted theoretical framework describing this joint development. Here, we propose a computational model of the development of active binocular vision to fill this gap. The model is based on a formulation of the active effi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…A more complete model would include a vergence control mechanism that controls the plane of fixation autonomously. Self-calibrating models capable of doing so have been proposed in the active efficient coding framework ( Zhao et al, 2012 ; Eckmann et al, 2020 ). Another potential avenue for future research is to focus on the stereoscopic networks and analyze whether the individual filters become sensitive to certain disparities that might help to ignore occluders.…”
Section: Discussionmentioning
confidence: 99%
“…A more complete model would include a vergence control mechanism that controls the plane of fixation autonomously. Self-calibrating models capable of doing so have been proposed in the active efficient coding framework ( Zhao et al, 2012 ; Eckmann et al, 2020 ). Another potential avenue for future research is to focus on the stereoscopic networks and analyze whether the individual filters become sensitive to certain disparities that might help to ignore occluders.…”
Section: Discussionmentioning
confidence: 99%
“…Receptive field properties in the early visual pathway ( Atick and Redlich, 1992 ; Olshausen and Field, 1996 ) as well as the tuning properties of auditory nerve fibers ( Lewicki, 2002 ; Smith and Lewicki, 2006 ) can emerge by efficiently encoding natural images or sounds, respectively. Recently, it was shown that efficient coding could also explain the simultaneous development of vergence and accommodation as a result of maximizing coding efficiency of the retinal signals ( Eckmann et al, 2020 ). There is currently a lot of interest whether higher-level representations can also be learned by efficient encoding of the retinal images ( Fleming and Storrs, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“… 22 , 33 , 34 , 36 , 100 Although amblyopia is most successfully treated during childhood when cortical plasticity remains high, the visual system retains considerable plasticity even in adulthood. 105 107 Efforts to identify and remove the factors that limit plasticity in adults have been promising, using methods such as perceptual learning, 108 video games, 109 dichoptic treatments, 110 and noninvasive brain stimulation. 111 113 Ongoing research into the nature of interocular suppression in amblyopia will enable refinement of these potential treatment approaches.…”
Section: Discussionmentioning
confidence: 99%